Laparoscopic supracervical hysterectomy using EnSeal vs standard bipolar coagulation technique: randomized controlled trial - Rothmund, Ralf; Kraemer, Bernhard; Brucker, Sara; Taran, Florin-Andrei; Wallwiener, Markus; Zubke, Andrea; Wallwiener, Diethelm; Zubke, Wolfgang (The journal of minimally invasive gynecology, 2013)
Objective - To compare the EnSeal device with standard bipolar coagulation forceps in laparoscopic supracervical hysterectomy (LASH). - Design - Prospective, randomized, controlled trial (Canadian Task Force classification I). - Setting - University hospital. - Patients - One hundred sixty patients who underwent LASH. - Intervention - Eighty patients underwent LASH using the EnSeal device (experimental group), and 80 patients underwent LASH using standard bipolar coagulation forceps (control group) (www.clinicaltrials.gov; study identifier NCT01806012). - Measurements and Main Results - Mean (SD) total operative time was 78.18 (33.96) minutes in the experimental group and 86.30 (35.34) minutes in the control group (p = .03). Documented blood loss was <50 mL in 72 patients in the experimental group and 62 patients in the control group (p = .03), and was 50 to 100 mL in 8 patients in the experimental group and 18 patients in the control group (p < .001). Postoperative hospital stay was significantly shorter for patients in the experimental group compared with the control group: 2.01 (0.44) days vs 2.17 (0.47) days, respectively (p = .03). There was no difference in postoperative pain scores and complications between the two treatment groups. - Conclusion - Total resection time was shorter in the experimental group, and the other investigated clinical parameters were not inferior in the experimental group compared with the control group. The results of the present study indicate that use of the EnSeal device is at least as reliable as the conventional electrocoagulation technique in LASH.
Gesehen am 21.01.2022